Maternal obesity causes fetal hypothalamic insulin resistance and disrupts development of hypothalamic feeding pathways - L. Dearden; S. Buller; I.C. Furigo; D.S. Fernandez-Twinn; S.E. Ozanne (Elsevier, 2020)
Objective: Perinatal exposure to maternal obesity results in predisposition of offspring to develop obesity later in life. Increased weight gain in offspring exposed to maternal obesity is usually associated with hyperphagia, implicating altered central regulation of food intake as a cause. We aimed to define how maternal obesity impacts early development of the hypothalamus to program lasting dysfunction in feeding regulatory pathways. Methods: Mice offspring of diet-induced obese mothers were compared to the offspring of lean control mothers. We analysed gene expression in the fetal hypothalamus, alongside neurosphere assays to investigate the effects of maternal obesity on neural progenitor cell proliferation in vitro. Western blotting was used to investigate the insulin signalling pathway in the fetal hypothalamus. Characterisation of cell type and neuropeptide profile in adulthood was linked with analyses of feeding behaviour. Results: There was a reduction in the expression of proliferative genes in the fetal hypothalamus of offspring exposed to maternal obesity. This reduction in proliferation was maintained in vitro when hypothalamic neural progenitor cells were grown as neurospheres. Hypothalamic fetal gene expression and neurosphere growth correlated with maternal body weight and insulin levels. Foetuses of obese mothers showed hypothalamic insulin resistance, which may be causative of reduced proliferation. Furthermore, maternal obesity activated the Notch signalling pathway in neonatal offspring hypothalamus, resulting in decreased neurogenesis. Adult offspring of obese mothers displayed an altered ratio of anorexigenic and orexigenic signals in the arcuate nucleus, associated with an inability to maintain energy homeostasis when metabolically challenged. Conclusions: These findings show that maternal obesity alters the molecular signature in the developing hypothalamus, which is associated with disrupted growth and development of hypothalamic precursor cells and defective feeding regulation in adulthood. This is the first report of fetal hypothalamic insulin resistance in an obese pregnancy and suggests a mechanism by which maternal obesity causes permanent changes to hypothalamic structure and function.